Transformative Learning as a Part of Living Theory: A Constant Evolution of Transformative Learning Theory in Lifelong Education - Misawa, Mitsunori (Adult Education Critical Issues, 2024)
Transformative Learning Theory is one of the major adult learning theories. It has gained significant attention due to its potential to revolutionize education and personal development. Although its popularity has made it branch out from the adult learning theories as a distinct theory with unique characteristics and utilizations, the field of Transformative Learning has fallen into its own disorienting dilemma. The field of Transformative Learning is now in a critical phase as a field of study where it needs to refine itself to better develop its identity and grow. In this article, I will respond to the six questions regarding Transformative Learning Theory and the field of Transformative Learning that the editorial team of the journal asks.